La publicidad televisiva en la ciudad de Loja, y su influencia en el comportamiento de compra del consumidor, durante el periodo octubre – diciembre 2013 - Ordoñez Celi, Johanna Socorro (2014)
The research work was part of a descriptive, analytical and explanatory study; concerning: TELEVISION ADVERTISING IN THE LOJA CITY , AND ITS INFLUENCE ON THE BEHAVIOR OF PURCHASE OF CONSUMER FOR THE PERIOD OCTOBER - DECEMBER 2013, which was organized and developed according to the standards of graduation in force, established by National University of Loja, prior to developing a general objective was formulated: To determine the influence of television advertising on consumer buying behavior in the city of Loja. The methods were applied: Scientist, inductive-deductive, Statistical and Historical; a sample of 400 people was established, to which was applied a survey to determine how television advertising in the city of Loja, influences the consumer buying behavior. In the interpretation of the application and analysis of the objectives, it became clear that all respondents are local channels, news programming preferred, most advertising has been presenting these TV channels; ensure recall certain advertisements for various reasons the music, the message, food dishes, promotions, prices and products needed to be, it is important to mention that ten advertisements that remind respondents that are studied, the description that Respondents indicated that 83% believe no influence when purchasing a product or requesting service, advertising does create a need but not choose the company or business that is standard in television, the decision is based on the needs that respondents food, medicines, or bazaar items for the home, saving needs or financial credits, or having to cancel compulsory basic services such as energy. Thus it is concluded that television advertising that pattern in the local TV channels, does not influence the buying behavior of the consumer, but if they create a need that is satisfied with the purchase of a product or service companies or other businesses chosen by the respondents; This research aims to provide a specific fact, with key features such as the present and past events, the causes of this particular fact, data search, consequences, and testimonials